Temple Art and Icon Painting at The Universities - the Spiritual Formation of Students in Russia - Rebinsky, G.A; Gamov, E.S; Martynova, A.V; Tonkovid, S.B (International Journal of Engineering and Technology, 2018)
This article shows the results of the research of the term "icon". The importance of icons in the Orthodox Church is shown. The main aspects of the methodology of making icons, traditions and modern problems in church art are described. The main aspects of the methodology of making icons, traditions and modern problems in church art are described. Information on achievements in the field of icon painting at the Lipetsk State Technical University is adduced. (FSEI HE Â«LSTUÂ»)